Digestão anaeróbia de polímero orgânico a base de fécula de mandioca - Cremonez, Paulo André (2015)
The increase in the generation and accumulation of solid residues mainly compounds for packaging, led to a search for development technologies of plastics and biodegradable films eligible for treatment by conventional processes used for organic materials. Currently, various plastics, expanded polystyrene and biodegradable films are produced from the most diverse forms. The present work aims to evaluate primarily anaerobic degradation of biodegradable polymers based on manioc starch. The dissertation is divided into two chapters, the first aims at assessing the anaerobic digestion of organic polymer based on manioc starch diluted in residual water of pigs in various concentrations. Meanwhile, the second chapter aims to compare the cassava-based biodegradable polymer with other material widely studied as an additive in the biodigestion process, the glycerol. The anaerobic biodigestion process proves to be effective in the degradation and stabilization of polymeric materials based on cassava and guarantee high rates of production of biogas, rich in methane that can be used for multiple purposes, ensuring energy savings in production processes. The polymer can still be considered interesting additive on digestion processes of other agro-industrial waste aimed at quickly increased production of biogas and showing superior results to other widely used additives as glycerol. Nevertheless, for easy and quick production material degradability of volatile acids, the addition of high concentrations of polymer is not indicated by the possibility of acidification of the reactors.